Bandwidth and Wavelength Tunable All-Optical Filter Based on Cascaded Opto-Mechanical Microring Resonators - Li Liu; Wei Xue; Xing Jin; Jin Yue; Zhihua Yu; Lina Zhou (IEEE Photonics Journal)
We propose and experimentally demonstrate an all-optical filter with tunable bandwidth and wavelength based on cascaded opto-mechanical microring resonators (MRRs). As the transmission of each MRR could be tuned by injecting resonance powers, the total transmission of the three cascaded MRRs could be manipulated to realize tunable all-optical filters. Due to the free-hanging waveguides of the opto-mechanical MRRs, the nonlinear effects in the device are efficiently enhanced, which contribute to reduce the resonance powers. In the experiment, the bandwidth and wavelength tunability of the optical filter have been demonstrated by injecting three resonance powers. The tuning efficiencies of the filter's 3 dB bandwidth and wavelength could reach 0.233 nm/mW and 0.043 nm/mW respectively, which benefit the construction of all-optical systems with low-power consumptions. The footprint of the compact device is 0.02 mm2. The proposed tunable optical filter is competent to process optical signals with dominant advantages of high tuning efficiencies, all-optical control, compact footprint, and complementary metal-oxide semiconductor-compatibility, which has significant applications for on-chip all-optical systems.